Implementation of DSP based SPWM for single phase inverter - Mohammad Faridun Naim, Tajuddin; N. H., Ghazali; Ismail, Daut, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/